Economic Viability of Efficiency Houses for Social Housing in Germany - Ziegler, Ferdinand; Robinson, Aaron (International Journal of Economics and Financial Issues, 2025)
In Germany, the construction of new residential buildings for social housing has significantly declined, while the demand for such housing has steadily increased. This study aimed to identify the economic conditions necessary to enable affordable rents for social housing in Germany, considering various financial and policy parameters. A mixed-methods approach was employed, utilizing both qualitative and quantitative data from 45 realized mid-range residential buildings meeting EH 40 and EH 55 energy standards. The methodology included detailed profitability calculations performed using the dynamic net present value method, incorporating variables such as investment costs, rent adjustments, discount rates, financing periods, and tax rates. Sensitivity analyses and Monte Carlo simulations were conducted to assess the impact of these variables on investment requirements and initial rent levels. The results indicate that rent adjustments have the greatest impact on required investments, followed by discount rates and financing periods. Specifically, a 0.5% increase in rent adjustment necessitates higher initial investment costs of approximately €124 per square meter per month. The simulations also highlighted the significant influence of discount rates on initial rents, with nearly one euro per square meter increase for a one percent rise in interest rates. The findings suggest that while current policies and subsidies help reduce investment costs, additional measures such as social funds are needed to ensure financial viability and affordability. In conclusion, the study highlights the need for comprehensive economic strategies to support the development of energy-efficient social housing in Germany. The implications of these findings are crucial for policymakers and investors aiming to balance economic viability with social sustainability.